Effects of Ethanolic Extract of Metracaria chamomela on Some Physiological Parameters in Male Rabbits - Ali, Alia Hussein (The Iraqi Journal of Veterinary Medicine, 2015)
The aim of this study is to explain the effect of Ethanolic extract 70% of Metracaria chamomella on some physiological parameters in male rabbits. Twelve adult male rabbits were used in this study and were divided equally into two groups: First group was control (C) and received normal saline for four weeks, the second group (Treated group) was intubated orally with ethanolic extract of Metracaria chamomella in a dose 70 mg/kg B.W. for four weeks. Blood samples were collected by heart puncture from each animal at the end of experiment. Blood sample was divided into a part for hematological study and a part for biochemical analysis. The value of serum urea, and creatinine were reduced in animals that received Metracaria chamomella extract at dose of 70 mg/ kg B.W. as compared with the control group. Significant decrease in serum activity of aspartate aminotransferase alanine aminotransferase and alkaline phosphatase activity was observed in Metracaria treated animal as compared with the control group. This study explained that there was significant increase in serum total protein, serum albumin and serum globulin in treated animals as compared with the control group. The value of total cholesterol, serum triacylglycerol, serum low density lipoprotein cholesterol and very low density lipoprotein cholesterol concentration were reduced significantly in animal received Metracaria chamomella extract while the high density lipoprotein cholesterol was elevated significantly as compared with control group. While the effect of Metracaria chamomella extract on blood picture showed no changes in red blood cell count, hemoglobin concentration and hematocrit value but showed significant decrease in platelet count, and significant increase in white blood cell count as compared with control group. Over all this study explained that Metracaria chamomella extract had Reno protective and hypolipidimic effect in male rabbit.